1998
DOI: 10.1364/ol.23.001556
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency guided-mode resonance filter

Abstract: A high-efficiency guided-mode resonance reflection filter is reported. The device consists of a surface-relief photoresist grating and an underlying HfO (2) waveguide layer deposited on a fused-silica substrate. The spectral response measured with a dye-laser beam at normal incidence exhibited a peak reflectance of 98% at a wavelength of 860 nm with sideband reflectance below approximately 5% extending over the wavelength range provided by the dye (800-900 nm). At normal incidence the filter linewidth was 2.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(126 citation statements)
references
References 14 publications
2
123
0
1
Order By: Relevance
“…Figure 13 shows our exciting experimental results where the peak reflectance reaches 100.2% normalized to bulk, deposited gold. Predicted gold reflectivity reaches 99.4% at these wavelengths so we may conclude that this device demonstrates comparable or better reflectivity than the published record of 98% 10 . The spectral FWHM is a narrow 4.14nm and perhaps more importantly, the sidebands across the wide spectral range remain low and flat (≤5%); close to our theoretical target of 4.3%.…”
Section: Measured Rsg Spectrasupporting
confidence: 49%
“…Figure 13 shows our exciting experimental results where the peak reflectance reaches 100.2% normalized to bulk, deposited gold. Predicted gold reflectivity reaches 99.4% at these wavelengths so we may conclude that this device demonstrates comparable or better reflectivity than the published record of 98% 10 . The spectral FWHM is a narrow 4.14nm and perhaps more importantly, the sidebands across the wide spectral range remain low and flat (≤5%); close to our theoretical target of 4.3%.…”
Section: Measured Rsg Spectrasupporting
confidence: 49%
“…It was also shown that GMR also occurs in PhC slab [38]. The narrow-band, 100% reflectivity has been experimentally demonstrated [39]. Recent improvements of semiconductor manufacturing process made it possible to fabricate SWGs made of high index materials such as Si.…”
Section: Guided-mode Resonancementioning
confidence: 92%
“…A RG functions basically as a wavelength selective mirror, and its reflection spectrum can be tailored by designing the periodic structure appropriately [18]. Highly efficient reflection [19], as well as the ability to tailor the spatial beam profile, has been successfully demonstrated [20]. Recently, attempts have been made to extend the GMR concept to curved substrate structures [21,22].…”
Section: Open Accessmentioning
confidence: 99%